PENERAPAN MEDIA CD PEMBELAJARAN DALAM MENINGKATKAN PRESTASI MATERI AKHLAK PADA SISWA - Agus Sutiono (Asaatidzah, 2022)
This research is focused on the use of Interactive Learning CD in teaching material about Respect and Obedience to Parents and Teachers at SDN Otista for grade 6 students. The focus of this research includes: Planning learning using Interactive Learning CD, learning processes using Interactive Learning CD , supporting factors and inhibiting factors in using the Interactive Learning CD about Respect and Path lessons to Parents and Teachers. The results showed in general it can be concluded that the use of Interactive Learning CD that have been implemented by teachers in Islamic Religious Education learning at SDN Otista Bogor can increase student learning activities, students' interest in learning to respect and obey parents and teachers, creating an exciting learning atmosphere. and fun, and develop students' ability to cooperate and participate in group activities. The learning outcomes achieved by students using the Interactive Learning CD show quite satisfactory results, as evidenced by the level of achievement of learning outcomes that exceed the minimum completeness criteria, including theoretical abilities and average scores.